Case Report: Herpes Simplex Virus Type 2 Acute Retinal Necrosis With Viral Encephalitis in Children - He, Luyao; Duan, Jialiang; Shang, Qingli (Frontiers in Medicine, 2022)
Background: Few cases on acute retinal necrosis with viral encephalitis in children have been reported, especially cases where the fundus cannot be identified due to severe vitreous opacity in the early stage, resulting in the difficult diagnosis of the condition. Methods: A retrospective review was conducted of an unusual case of herpes simplex virus-2 (HSV-2) acute retinal necrosis with viral encephalitis in an immunocompetent child along with the relevant literature published up to October 2020. Result: An 11-year-old girl presented with a 20-day history of ocular redness and decreased visual acuity in the left eye. Examination revealed anterior uveitis and vitreous opacity in the left eye. Anterior chamber tap was performed because the fundus could not be observed clearly, and the aqueous humor was positive for HSV-2 DNA. Cerebrospinal fluid also tested positive for HSV-2. The patient was diagnosed with acute retinal necrosis syndrome and viral encephalitis. The condition was controlled with timely antiviral and steroid therapy. The patient was also treated with prophylactic laser therapy to prevent retinal detachment during subsequent follow-up. The pathogenesis, diagnosis, and treatment of HSV-2 acute retinal necrosis in children and the association between acute retinal necrosis and viral encephalitis are further discussed based on the published literature. Conclusion: Pediatric acute retinal necrosis caused by HSV-2 may be due to the acquisition of subclinical infection with HSV-2 during parturition, followed by reactivation of the virus latent in the body on account of certain factors. Moreover, it may be complicated by viral encephalitis. For suspected cases with invisible fundus, early intraocular fluid examination is significantly helpful for differential diagnosis. Early diagnosis, early treatment, and timely prophylactic laser treatment to prevent retinal detachment are keys to a better prognosis. Physicians need to pay attention to such suspected cases during diagnosis and treatment.